ПРАВОВАЯ ИДЕОЛОГИЯ КАК ФАКТОР ФУНКЦИОНИРОВАНИЯ И РАЗВИТИЯ ПРАВОВОЙ СИСТЕМЫ УКРАИНЫ - Пампура, Максим Валерьевич (SUPREMANCE OF LAW, 2017)
The content of the notion «legal ideology» is reveal. The role and significance of legal ideology in the transformational societies are defined. The main directions of the impact of legal ideology in the functioning and development of the legal system of Ukraine are analyzed.